Hubungan Fear Of Missing Out dengan Compulsive Buying pada Pengguna Instagram di Fakultas Komunikasi Universitas Bina Darma Palembang - Nuraisyah, Siti; Marita Lasutri Tama, Mulia (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
Researchers intend to conduct research with the aim of knowing the relationship between fear of missing out (FoMO) on compulsive buying behavior. The objectives of this study are: To see the relationship between Fear of Missing Out (FoMO) and compulsive buying behavior among Instagram users at the Faculty of Communication at Bina Darma University Palembang, aged 18 to 25 years. The research approach used in this research is quantitative. Data collection in this study was conducted in a survey using a scale to describe trends, attitudes and opinions. The population taken by the researcher was Communication Faculty students who actively played Instagram at Bina Darma University Palembang. The overall sample is 149 respondents. Data analysis was carried out to test hypotheses to determine conclusions in order to achieve research objectives. Based on the results of the research and discussion that has been carried out, it can be concluded that there is a significant relationship between fear of missing out and compulsive buying of students at the Faculty of Communication, University of Bina Darma. The majority of Bina Darma University communication faculty students have a high sense of compulsive buying and fear of missing out.